La influencia de las políticas de responsabilidad social y la pertenencia a redes de cooperación en el capital relacional y estructural de las microempresas - Sonia Benito Hernández; Pablo Esteban Sánchez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– Micro.enterprises have certain attributes that distinguish them from large companies and from those that see problems when adopting principles and social responsibility policies. However, the principles of social responsibility can and should be integrated into any organization, including micro.enterprises. In this paper, we study how cooperation networks could be an appropriate incentive for the micro.enterprises to implement social responsibility policies, strengthening some advantages and mitigating some disadvantages that micro.enterprises may have when dealing with such policies, and enhancing, ultimately, the level of development of their relational and structural capital. In preparing the study theoretical model is proposed that analyses the components of these types of capital in the company, adapted to the micro.enterprise as well as studying the influences that social responsibility policies and membership of cooperation networks can have on these components.
Keywords: M10; M12; M13; M14; L14; 650; networking; micro-enterprise; social responsibility; relational and structural capital